Treatment of tumour tissue with radio‐frequency hyperthermia (using antibody‐carrying nanoparticles) - Reza Didarian; Ibrahim Vargel (IET Nanobiotechnology)
Abstract Intelligent inorganic nanoparticles were designed and produced for use in imaging and annihilating tumour cells by radio‐frequency (RF) hyperthermia. Nanoparticles synthesised to provide RF hyperthermia must have magnetite properties. For this purpose, magnetite nanoparticles were first synthesised by the coprecipitation method (10–15 NM). These superparamagnetic nanoparticles were then covered with gold ions without losing their magnetic properties. In this step, gold ions are reduced around the magnetite nanoparticles. Surface modification of the gold‐coated magnetic nanoparticles was performed in the next step. A self‐assembled monolayer was created using cysteamine (2‐aminoethanethiol) molecules, which have two different end groups (SH and NH2). These molecules react with the gold surface by SH groups. The NH2 groups give a positive charge to the nanoparticles. After that, a monoclonal antibody (Monoclonal Anti‐N‐CAM Clone NCAM‐OB11) was immobilised by the 1‐ethyl‐3‐(3‐dimethylaminopropyl)carbodiimide/N‐hydroxysuccinimide method. Then, the antenna RF system (144.00015 MHz) was created for RF hyperthermia. The antibody‐nanoparticle binding rate and cytotoxicity tests were followed by in vitro and in vivo experiments. As the main result, antibody‐bound gold‐coated magnetic nanoparticles were successfully connected to tumour cells. After RF hyperthermia, the tumour size decreased owing to apoptosis and necrosis of tumour cells.